2018
DOI: 10.1149/08606.0031ecst
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectricity of HfxZr1−xO2 Thin Films Fabricated Using TiN Stressor and ZrO2 Nucleation Techniques

Abstract: We studied the ferroelectricity and the leakage current (J) properties of two types of the MFM capacitors such as the TiN/ZrO2/HfxZr1−xO2/ZrO2/TiN capacitor (D-ZrO2) with the ZrO2 nucleation layers, comparing to the TiN/HfxZr1−xO2/TiN capacitor (D-TiN) with the TiN stressor layers. The larger ferroelectric phase ratio was achieved by the epitaxial like grain growth of the HfxZr1−xO2 film on the surface of the top- and bottom-ZrO2 nucleation layers. Thus, the larger remanent polarization (2P r = 29 µC/cm2) of D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…(a) P-V hysteresis loops at 300 K of different HZO samples, (b) comparison of FE performance between the HZO/VO x -1.67 sample and previous HZO-based capacitors (note: data are obtained from refs and plotted by the authors). In panel (b), capping layer materials are indicated at the corresponding data points, while the bottom electrode and seed layer materials are represented by the colors of the data points that are illustrated in the right of the panel.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(a) P-V hysteresis loops at 300 K of different HZO samples, (b) comparison of FE performance between the HZO/VO x -1.67 sample and previous HZO-based capacitors (note: data are obtained from refs and plotted by the authors). In panel (b), capping layer materials are indicated at the corresponding data points, while the bottom electrode and seed layer materials are represented by the colors of the data points that are illustrated in the right of the panel.…”
Section: Resultsmentioning
confidence: 99%
“…Solutions to these scaling and integration issues may lie in the recently emerging HfO 2 -based FE materials. Ferroelectricity in HfO 2 -based FE materials originates from a noncentrosymmetric orthorhombic phase (o-phase; space group: P ca 2 1 ). Theoretically, this o-phase can exhibit a remnant polarization ( P r ) as high as 50 μC/cm 2 . However, the experimental P r values of HfO 2 -based FE materials reported in recent years were limited to the range of ∼10–20 μC/cm 2 , well below the theoretical value. In addition, the coercive field ( E c ) values of HfO 2 -based FE materials were typically 1–2 MV/cm, about one order of magnitude higher than those of traditional FE materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This concept is based on the superior characteristics of ZrO 2 films processed via the low-temperature ALD process at 300 °C (e.g., good crystallinity and predominantly o/t/c-phases). The HZO-based MFM capacitors with a ZrO 2 nucleation layer exhibited the improvement of their ferroelectricity, while those with an amorphous Al 2 O 3 layer showed smaller 2 P r compared to the conventional HZO-based MFM capacitors. , Here, the effect of the ZrO 2 layer on the ferroelectricity of the MFS structure was investigated. Figure a,b shows cross-sectional TEM images of MFS capacitors without ZrO 2 (w/o) and ZrO 2 -10 nm following the PMA process at 300 °C.…”
Section: Interface Engineeringmentioning
confidence: 99%
“…In this work, atomic-layer deposited (ALD) ZrO 2 thin films were introduced as ILs with sufficiently good interface between the Si and good leakage current characteristics without any introduction of additional SiO 2 interfacial layer for the MFIS capacitors using ferroelectric HZO layers. The ZrO 2 thin films have been employed as seed layers for expediting the crystallization process of the ferroelectric HZO layers for the metal-ferroelectric-metal (MFM) and MFIS capacitors [22,23]. Xiao et al demonstrated the ferroelectric MW as wide as 2.8 V for the capacitors with TaN/HZO/ZrO 2 /SiO 2 /Si structure [24], but in-depth discussions on the detailed design schemes to optimize the device performance were not provided.…”
Section: Introductionmentioning
confidence: 99%